Method for Estimating Optimum Free Resonant Frequencies in Overcoupled WPT System - Dong-Wook Seo; Jae-Ho Lee (International Journal of Antennas and Propagation)
In our previous work, we proposed the method to maximize the output power even in the overcoupled state of the wireless power transfer (WPT) system by controlling free resonant frequencies and derived closed-form expression for optimum free resonant frequencies of the primary and secondary resonators. In this paper, we propose the mutual coupling approach to derive the optimum free resonant frequencies and show the measured power transfer efficiency (PTE) using the transmission efficiency as well as the system energy efficiency. The results of the proposed approach exactly coincide with those of the previous work, and the fabricated prototype achieves the transmission efficiency of about 80% by tuning the free resonant frequencies to the optimum values in the overcoupled state.